Resolving the (Apparent) Talker Recognition Paradox in Developmental Speech Perception. (10th April 2019) - Fecher, Natalie; Paquette‐Smith, Melissa; Johnson, Elizabeth K.
Abstract : The infant literature suggests that humans enter the world with impressive built‐in talker processing abilities. For example, newborns prefer the sound of their mother's voice over the sound of another woman's voice, and well before their first birthday, infants tune in to language‐specific speech cues for distinguishing between unfamiliar talkers. The early childhood literature, however, suggests that preschoolers are unable to learn to identify the voices of two unfamiliar talkers unless these voices are highly distinct from one another, and that adult‐level talker recognition does not emerge until children near adolescence. How can we reconcile these apparently paradoxical messages conveyed by the infant and early childhood literatures? Here, we address this question by testing 16.5‐month‐old infants ( N  =   80) in three talker recognition experiments. Our results demonstrate that infants at this age have difficulty recognizing unfamiliar talkers, suggesting that talker recognition (associating voices with people) is mastered later in life than talker discrimination (telling voices apart). We conclude that methodological differences across the infant and early childhood literatures—rather than a true developmental discontinuity—account for the performance differences in talker processing between these two age groups. Related findings in other areas of developmental psychology are discussed.